THE EFFECT OF IMPLEMENTING PODCAST IN ENHANCING STUDENTS’ SPEAKING ACHIEVEMENT IN THE FULLY DIGITAL ERA - Wulan, Oktavia Retno Nawang (PEOPLE: International Journal of Social Sciences, 2018)
In the current century, the appropriation of technological platforms which requires new approaches for education should be fostered to today’s youth, often referred as digital natives, since they are growing up surrounded and immersed in rapid technological development. The purpose of the present study aims to investigate whether the implementation of technological platforms in language teaching and learning, focused on the implementation of podcast, helps the students to enhance their speaking achievement. This experimental study was administered to the eleventh grade students of science program in which they were assigned into experimental and control group randomly. To assess the students’ speaking performances in the post-test, analytic scoring rubric covering content, fluency, accuracy on pronunciation, grammar, and spelling was involved. From the data analysis, the value of significance column (2-tailed) was 0.025, which was lower than 0.05 (p<0.05). Consequently, the formulated null hypothesis (H0) was rejected. Regarding the result of this research, the implementation of podcast showed a significant effect on the eleventh grade students’ speaking achievement. Further, the implementation of podcast generated the students to be motivated and challenged in the speaking class. For future scope, the current study suggested that EFL students have to be familiarized with the integration of podcasting technology in language learning in order to get better gains in all language skills, viz.: listening, reading and writing as it showed a significant effect in this study.